Прости грехи наши - Сарду Ромэн (Европейский BEST, 2006)
Экземпляры: ф.11 (20180320) / Инвентарный номер: 58142 / Цена: / Сис.шифр: 84(4Фра)-4 / Авт.знак: С 20 / ГРНТИ: 17.82.30 / ББК: 84(4Фра)-4^VLBC/RL